Challenging the Hegemony of Western Views of Learning - Sharan B. Merriam; Logama Doraisamy; Brian Findsen; Mazalan Kamis; Youngwha Kee; Mazanah Mohamad; Gabo Ntseane; Swathi Nath Thaker (Adult Education Research Conference, 2005)
This symposium will challenge the hegemony of Western conceptions of learning through the presentation of conceptions of knowing and learning based in alternative epistemological systems. The following views of knowing and learning will be presented: Confucian, Hindu, Maori, Islamic, and African Indigenous Knowledge.